1996
DOI: 10.1097/00006534-199609000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Inframammary Fold: What Are We Leaving Behind?

Abstract: Preservation of the inframammary fold (IMF) at the time of mastectomy facilitates immediate breast reconstruction. Twenty-four IMF specimens were removed separately after mastectomy for cancer, were serially sectioned, and were examined histologically. Computer image analysis was used to calculate the percentage of breast tissue in each specimen. The mean volume of IMF tissue removed was 99 cm3 (27.3-205.2 cm3), and the mean area examined histologically was 3,036.3 mm2 (294-11,755 mm2). Breast tissue was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 3 publications
1
33
0
1
Order By: Relevance
“…Concerns have been raised about the increased residual breast tissue remaining after SSM because of the length of the skin flaps and retention of the inframammary fold. Carlson et al used computer image analysis to examine the inframammary fold tissue retained with a SSM [20]. Residual breast tissue was identified in 13 of 24 specimens but was correlated to only 0.02% of the total tissue volume removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns have been raised about the increased residual breast tissue remaining after SSM because of the length of the skin flaps and retention of the inframammary fold. Carlson et al used computer image analysis to examine the inframammary fold tissue retained with a SSM [20]. Residual breast tissue was identified in 13 of 24 specimens but was correlated to only 0.02% of the total tissue volume removed.…”
Section: Discussionmentioning
confidence: 99%
“…Barton et al demonstrated equivalent amounts of residual glandular breast tissue remaining on the anterior chest walls of 27 patients who had undergone SSM compared to 28 patients following total mastectomy, based on multiple chest wall biopsies [21]. The fact that histologic examination of LR rarely shows identifiable breast tissue has been highlighted by others [20]. Some researchers have proposed that skin and subcutaneous recurrences may be a result of residual tumor cells that were separate from an adequately resected cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Преимущество было достигнуто за счет сохранения есте-ственных границ молочной железы, определяемое основа-нием кожных лоскутов и в первую очередь инфрамаммар-ной складки. Несмотря на скептицизм, некоторые хирурги оставляли порой значительное количество ткани в этой области для улучшения эстетических результатов [36]. При этом клинически-патоморфологическая работа Barton et al продемонстрировала эквивалентное количе-ство резидуальной ткани в области лоскутов и поверхно-сти грудных мышц при «тотальной железистой мастэкто-мии» (total glandular mastectomy) и обычной радикальной мастэктомии с сохранением грудных мышц [37].…”
Section: современные модификации мастэктомии в сочетании с одномоментunclassified
“…Inframammary fold is not always obliterated during mastectomy and preserving the original ligamentous structure the inset of the flap above the fold will give the desired esthetic result. 15 Nevertheless, it is often difficult to define and place the inframammary crease at the appropriate level with this method. 9,13 Moreover, the patch-like appearance may have an unfavorable visual impact due to the additional border at the edge of the skin paddle that is very close and parallel to the inframammary fold.…”
Section: Restifomentioning
confidence: 99%